Evaluation of mechanical, microstructures and wear behaviours of aluminium alloy reinforced with mussel shell powder for automobile applications - Suleiman, Idawu Yakubu (Strojniški vestnik, 2021)
This paper aims to investigate the mechanical (tensile, hardness, impact, elongation), microstructure and wear behaviours of aluminium alloy reinforced with mussel shell powder (MSP) at different weight percentages (0 wt. % to 15 wt. %) at 3 wt. % interval. The mussel shell powder was characterized by X-ray fluorescence (XRF). The matrix and the composites% morphology were studied using a scanning electron microscope attached with energy dispersive spectroscopy for the distribution of mussel shell powder particles within the matrix. The wear behaviour of the alloy and composites produced at various reinforcements were carried out using a Taber abrasion wear-testing machine. The XRF showed the compositions of MSP to contain calcium oxide (95.70 %), silica (0.83 %) and others. Mechanical properties showed that tensile values increase with increases in MSP, hardness value increases from 6 wt. % to 15 wt. % of MSP. The impact energy decreased from 42.6 J at 3 wt. % to 22.6 J at 15 wt. %; the percentage elongation also decreased from 37.4 % at 3 wt. % to 20.5 % at 15 wt. % MSP, respectively. The bending stress results increase with increases in the percentage of reinforcement. The morphologies revealed that uniform distribution of MSP within the matrix resulted to improvement in mechanical properties. The wear resistance of the composites increases with increase in the applied load and decreases with increases in the weight percentage of MSP and can be used in the production of brake pads and insulators in the automobile industry.
Keywords: aluminijeve zlitine; aluminium alloy; composites; kompoziti; mechanical properties; mehanske lastnosti; microstructures; mikrostrukture; mussel shell powder; obrabne lastnosti; prašek iz školjčnih lupin; wear behaviour